2013
DOI: 10.1534/genetics.112.148106
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans PIG-1/MELK Acts in a Conserved PAR-4/LKB1 Polarity Pathway to Promote Asymmetric Neuroblast Divisions

Abstract: Asymmetric cell divisions produce daughter cells with distinct sizes and fates, a process important for generating cell diversity during development. Many Caenorhabditis elegans neuroblasts, including the posterior daughter of the Q cell (Q.p), divide to produce a larger neuron or neuronal precursor and a smaller cell that dies. These size and fate asymmetries require the gene pig-1, which encodes a protein orthologous to vertebrate MELK and belongs to the AMPK-related family of kinases. Members of this family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 66 publications
2
47
0
Order By: Relevance
“…It has been proposed that this is achieved through the asymmetric presence or activity in the two daughter cells of activators and/or repressors of the cell death fate and egl-1 transcription (Guenther and Garriga 1996;Frank et al 2005;Hatzold and Conradt 2008;Chien et al 2013). Indeed, mutations that affect the abilities of mothers of cells programmed to die to divide asymmetrically can affect the cell death fate of their daughters (Guenther and Garriga 1996;Cordes et al 2006;Hatzold and Conradt 2008;Ou et al 2010;Singhvi et al 2011;Chien et al 2013;Gurling et al 2014;Teuliere et al 2014). Therefore, events that lead to the polarization of mothers of cells programmed to die and that are required for their abilities to divide asymmetrically are fundamentally important for cell death specification.…”
Section: Role Of Asymmetric Cell Divisionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been proposed that this is achieved through the asymmetric presence or activity in the two daughter cells of activators and/or repressors of the cell death fate and egl-1 transcription (Guenther and Garriga 1996;Frank et al 2005;Hatzold and Conradt 2008;Chien et al 2013). Indeed, mutations that affect the abilities of mothers of cells programmed to die to divide asymmetrically can affect the cell death fate of their daughters (Guenther and Garriga 1996;Cordes et al 2006;Hatzold and Conradt 2008;Ou et al 2010;Singhvi et al 2011;Chien et al 2013;Gurling et al 2014;Teuliere et al 2014). Therefore, events that lead to the polarization of mothers of cells programmed to die and that are required for their abilities to divide asymmetrically are fundamentally important for cell death specification.…”
Section: Role Of Asymmetric Cell Divisionmentioning
confidence: 99%
“…The Q lineage: A number of genes have been identified that are required for the asymmetric divisions of the left and right posterior daughter of the Q cell (Q.p) during the first larval stage (L1 stage) and the apoptotic deaths of their smaller daughters (Cordes et al 2006;Ou et al 2010;Singhvi et al 2011;Chien et al 2013;Gurling et al 2014;Teuliere et al 2014). [Q.pL and Q.pR divide asymmetrically and each gives rise to a larger daughter, Q.pa, which further divides to generate two neurons (AVM/PVM and SDQL/SDQR, respectively), and a smaller daughter, Q.pp, which dies (Sulston and Horvitz 1977).]…”
Section: Role Of Asymmetric Cell Divisionmentioning
confidence: 99%
See 2 more Smart Citations
“…In brewers yeast, a member of Opisthokonta, a phylogenetic group that contains the holozoans as well as the fungi, the cytoplasmic protein Mo25 is essential for elongating growth and regulation of cell division [36]. This protein also exists in animals, where it mediates A/B-related cell shape changes during embryogenesis [37]. In regulating cell polarity, Mo25 operates in conjunction with the enzyme Lkb1 [38], which not only has a homologue in brewers yeast, but also in the more distantly related social amoebae Dictyostelium discoideum, where it is also involved in morphogenesis [39].…”
Section: 'Liquid Tissues' and The First Animalsmentioning
confidence: 99%